2011
DOI: 10.1021/jp2084555
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of Organic Field-Effect Transistors with Blend Pentacene/Anthradithiophene Films

Abstract: By taking advantage of the similarity between pentacene (PEN) and anthradithiophene (ADT) in molecular dimension and charge transport property, we have produced organic field-effect transistors (OFETs) with active layers consisting of well-blended PEN/ADT films. The blend-films were characterized by atomic force microscopy, X-ray diffraction, and soft X-ray spectroscopies. It is found that the blend-films containing no more than 10% of ADT exhibit a single-phase structure, large crystallinity, and improved oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The effective field-effect mobilities, threshold voltages, subthreshold swings, and on/off current ratios extracted from the transfer curves are summarized in Table . The largest effective mobilities we have obtained for tetraceno­[2,3- b ]­thiophene (0.55 cm 2 V –1 s –1 ), anthradithiophene (0.14 cm 2 V –1 s –1 ), and pentacene (1.14 cm 2 V –1 s –1 ) in the saturation regime are similar to the highest mobilities reported in the literature for these semiconductors (tetraceno­[2,3- b ]­thiophene, 0.47 cm 2 V –1 s –1 ; , anthradithiophene, 0.09 cm 2 V –1 s –1 ; pentacene, ∼1 cm 2 V –1 s –1 ). For anthradithiophene, it should be noted that a mixture of syn and anti isomers was employed in our work, as in ref . For TFTs based on isomerically pure ADT, Mamada et al and Nakano et al .…”
Section: Resultssupporting
confidence: 85%
“…The effective field-effect mobilities, threshold voltages, subthreshold swings, and on/off current ratios extracted from the transfer curves are summarized in Table . The largest effective mobilities we have obtained for tetraceno­[2,3- b ]­thiophene (0.55 cm 2 V –1 s –1 ), anthradithiophene (0.14 cm 2 V –1 s –1 ), and pentacene (1.14 cm 2 V –1 s –1 ) in the saturation regime are similar to the highest mobilities reported in the literature for these semiconductors (tetraceno­[2,3- b ]­thiophene, 0.47 cm 2 V –1 s –1 ; , anthradithiophene, 0.09 cm 2 V –1 s –1 ; pentacene, ∼1 cm 2 V –1 s –1 ). For anthradithiophene, it should be noted that a mixture of syn and anti isomers was employed in our work, as in ref . For TFTs based on isomerically pure ADT, Mamada et al and Nakano et al .…”
Section: Resultssupporting
confidence: 85%
“…The active semiconducting layer of the blended‐OPT contains only 9 wt% of OSC, while the major component of the film is the PLA. It has been reported that blending polymer into the OSCs can significantly reduce the material cost and enhance the processability by cost‐efficient solution methods during OFET fabrication . Here, we demonstrated that blending the PLA into the OSC could lead to OFETs with decent transistor characteristics and enhanced photosensitivity.…”
Section: Resultsmentioning
confidence: 60%
“…Blending OSCs with polymers in the conducting channels can provide the device with a large area of interaction interface, and thus is expected to enhance the photosensitivities of aforesaid novel OPTs. Meanwhile, fabrication of OPTs combining OSC and polymer blends effectively reduces the material cost, provides the devices with better flexibility, and importantly, tunes the OSCs properties to make the semiconducting materials printable . In this work, OPTs based on blended structure (blended‐OPTs) and layered structure (layered‐OPTs) were both fabricated by using a common soluble OSC 2,7‐dioctyl[1]benzothieno[3,2‐b][1]benzothiophene (C8‐BTBT) and an insulating biopolymer polylactide (PLA), and the photoresponse performances of both OPTs under UV light were investigated and compared.…”
Section: Introductionmentioning
confidence: 99%
“…But the key issue regarding the wide-spread production of organic electronic devices is the long term stability in ambient operating conditions. It is found that the device performance of vacuum evaporated organic semiconducting thin films is degraded by ambient environment [9][10][11] . Therefore, the real atmospheric effect on the electronic structure with time is immensely important to study for making more developed realistic devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Significant efforts have been made for making the performance of rubrene based TFTs better. In addition, few studies were carried out to understand transport and electronic properties of rubrene TFT. But the key issue regarding the widespread production of organic electronic devices is the long term stability in ambient operating conditions. It is found that the device performance of vacuum evaporated organic semiconducting thin films is degraded by ambient environment. Therefore, the real atmospheric effect on the electronic structure with time is immensely important to study for making more developed realistic devices. It has long been known that rubrene solution converts into rubrene-endoperoxide in the presence of oxygen and UV light .…”
Section: Introductionmentioning
confidence: 99%